Cathodic Protection by Distributed Sacrificial Anodes – A New Cost-Effective Solution to Prevent Corrosion of Subsea Structures - Iannuzzi, Mariano; Årtun, L.; Quale, G.; Johnsen, R. (2017)
Sacrificial anodes combined with organic coatings are the main strategy used to prevent corrosion on equipment submerged in seawater. Depending on the design life of the system, the size and complexity of the structure to be protected, and the environmental conditions, the total anode mass required to provide cathodic protection (CP) can be substantial. For subsea structures, the anode mass not only increases fabrication costs but also affects the total structure weight to an extent that may put special requirements on lifting vessels and cranes. Thermal Spray Aluminum (TSA) can be used to reduce anode demand or to extend anode life on projects with long design lives (i.e., 40 to 50 years). However, for subsea structures, TSA has not been used to replace the functionality of sacrificial anodes. In conventional CP design, TSA should not degrade while it remains connected to the CP system, draining current from sacrificial anodes, which ensure adequate cathodic protection. In this paper, a new concept named CP by distributed sacrificial anodes (DSA) is presented. The main principle of CP by DSA is to convert cathode area to anode area by distributing anode mass over the surface of the equipment to be protected. CP by DSA is achieved by the deposition of either a dual- or a single-layer metallic coating. In this work, DSA was applied by thermal spray (TS). DSA reduces the total exposed cathode area to small defects and imparts active cathodic protection, further reducing the current demand to be supplied by traditional, cast anodes. Results from exposure testing in flowing natural seawater at 10°C are discussed. Freely exposed samples thermally sprayed with DSA and conventional TSA as well as galvanic couplings between DSA, TSA, conventional anodes, and carbon steel with various area ratios were investigated. The electrochemical performance of DSA and conventional TSA was compared with that of traditional sacrificial anodes. Creviced UNS S31603 (AISI 316L) samples coupled to DSA coated plates in seawater at 10 and 35°C were also evaluated.